Aplicação da teoria de controle supervisório à planta de produção de hidrogênio do Parque Tecnológico Itaipu - Quispe, Angel Ambrocio (2020)
Nowadays, process industries are looking for efficiency and cost reduction to improve market competitiveness. Therefore, automation technology plays a fundamental role in the industry through the coordination of subsystems, so that individual operations and the overall functioning of the system are guaranteed, but also by the possibility of having greater control over the production process, and product quality. Hydrogen Power Plants (PPH) are infrastructures that need these automation technologies, in order to optimize the performance of the production process. The present work proposes the application of an approach for the implementation of a logical control of the subsystems and another approach for the sequential control of the operation of the PPH installed at the Technologic Park Itaipu (PTI). The first one is based on the application of the Supervisory Control Theory (TCS), to provide an automatic synthesis process for minimally restricted controllers. For the modeling, regular language was used in the form of deterministic automata of finite states, which were applied to model the free behavior and the specifications of logical control of the plant subsystems. Also, it was discussed the architecture for implementing TCS in Programmable Logic Controllers (PLCs) and the methodology for implementing a control project. The second approach is based on the development of a flowchart where the sequence of states of operation of the hydrogen production cycle was modeled. To verify these two approaches, a laboratory benchtop that represents PTI's hydrogen plant was built and the codes of both approaches were implemented in PLC's. The results obtained demonstrate the systematization, flexibility and efficiency to carry out the design of system control of a hydrogen plant, in addition to allowing the structuring and verification of these in a laboratory benchtop.